Knowledge and practices in the use of antibiotics among a group of Nigerian university students - Igbeneghu, Oluwatoyin Abimbola (International Journal of Infection Control, 2013)
The study examined the knowledge and practice of antibiotic use among students in a university in south western Nigeria. A questionnaire was administered to each of 500 students drawn from all the Departments in the university excluding those from the faculty of Pharmacy, Health Sciences and Department of Microbiology.A response rate of 99.2% was obtained from the respondents. The most commonly used antibiotics were tetracycline and amoxicillin. The aim of antibiotic use for common cold was observed in 32.3% of the respondents while 17.7% used antibiotics for sore throat. Majority of the participants (72.4%) used the same antibiotics as previously prescribed by their doctors to treat their perceived infections while 51.2% kept left over antibiotics with the intention of future use. More than half (55%) of the students stopped taking their antibiotics when they felt better or when the symptoms of their infections appeared to have stopped. The students’ rating of their sources of antibiotics and prescription for antibiotics indicated that most of the students do not know the appropriate sources from where to purchase their antibiotics nor do they know the appropriate persons from whom to obtain a prescription for antibiotics.The study showed a high rate of consumption of antibiotics among university undergraduates who mostly obtain their antibiotics without a physician’s prescription from unofficial sources and do not complete their course of antibiotic therapy. The education of these students on the appropriate use of antibiotics will go a long way in improving the students’ attitude towards antibiotics.